2016
DOI: 10.1021/acs.orglett.6b01987
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselective Hydrosilylation of Unsymmetrical Alkynes Catalyzed by a Well-Defined, Low-Valent Cobalt Catalyst

Abstract: Herein, the use of a well-defined low-valent cobalt(I) catalyst [HCo(PMe3)4] capable of performing the highly regio- and stereoselective hydrosilylation of internal alkynes is reported. The reaction can be applied to a variety of hydrosilanes, symmetrical and unsymmetrical alkynes, giving in many cases a single hydrosilylation isomer. Experimental and theoretical studies suggest the key step to be a hydro-cobaltation and that the reaction proceeds through a classical Chalk-Harrod mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 48 publications
(19 reference statements)
3
38
0
Order By: Relevance
“…Under these circumstances, low‐toxic, inexpensive, and earth‐abundant base metals (e.g., Fe, Ni, and Mn) have proven to be promising alternatives. In particular, cobalt complexes that show high regio‐ and stereoselectivity have been developed rapidly in recent years (Scheme ) . For instance, Deng and co‐workers developed a three‐coordinate cobalt(I) complex that catalyzed the hydrosilylation of alkynes to synthesize ( E )‐β‐vinylsilanes with high regioselectivity (Scheme a‐I) .…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, low‐toxic, inexpensive, and earth‐abundant base metals (e.g., Fe, Ni, and Mn) have proven to be promising alternatives. In particular, cobalt complexes that show high regio‐ and stereoselectivity have been developed rapidly in recent years (Scheme ) . For instance, Deng and co‐workers developed a three‐coordinate cobalt(I) complex that catalyzed the hydrosilylation of alkynes to synthesize ( E )‐β‐vinylsilanes with high regioselectivity (Scheme a‐I) .…”
Section: Introductionmentioning
confidence: 99%
“…As for unsymmetrical internal alkynes without directing groups,c obalt-catalyzedh ydrosilylation reactions generate highly selective syn-adduct products difficultly. [13][14][15][16][17] Herein, we firstly reported ah ighly syn-adducts-selective hydrosilylation of unsymmetricali nternal alkynesw ith Ph 2 SiH 2 using heterocatalysis system. All reactions were excellentlys elective for the formationo ft he syn-a-vinylsilane products (r.r.…”
Section: Resultsmentioning
confidence: 99%
“…Petit's group reported low-valent cobalt(I) HCo(PMe 3 ) 4 catalyzed unsymmetrical internal alkynes hydrosilylation suffers from good regioselectivity,b ut as eries of internal alkynes have poor regioselectivity. [17] Consequently,h ydrosilylation of unsaturated hydrocarbon with homogeneous catalysts finds industriala pplications including fluids, molding products, silicone-based surfactants and releasec oatings. [18] However,p roblems such as competing side reactions, catalyst activation,c atalysts eparation and regeneration have still persisted.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Much less attention has been directed towards cobalt-catalyzed hydrosilylations of alkynes which often require high catalyst loadings, complex ligands, and harsh conditions or showed poor regio/stereocontrol or a limited substrate scope with regard to alkynes and silanes ( Scheme 1 , top). 7 12 Very recently, Ge et al reported Co-catalyzed hydrosilylations to give ( Z )-vinylsilanes in the presence of pyridine-2,6-diimines. 13 We believed that a most user-friendly protocol would combine the following criteria: (i) high catalytic activity of a commercial catalyst system under very mild conditions; (ii) control of regioselectivity and stereoselectivity by the choice of the ligand, and (iii) a wide substrate scope involving terminal and internal alkynes and trihydrosilanes.…”
mentioning
confidence: 99%
“…These results are a significant extension of previous reports with N,N,N-ligands that resulted in poor regio-selectivity with PhSiH 3 . 12 The strict ligand control of this protocol is further documented by the lack of catalytic activity in the presence of other N,N-ligands such as (pyridin-2-yl)methanimine, butane-2,3-diimine, and terpyridine (entries 13 and 14).…”
mentioning
confidence: 99%